Buddhist education and propagation in Lao PDR. - Somepanno, Sombath (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2020)
Education is resumption of value, knowledge, ability, position and behavior, which in meaning of education wide is living itself (and the learning for a lifetime), as process removes stupidity and matures self towards perfection. This definition comes near sociological sight, psychological and anthropological. Learning to know, leaning to do, and Learning to communicate, in order to know or to do is three different categories of teaching three different kinds of learning experience.